Monotocy and the evolution of plural breeding in mammals. (6th May 2020) - Lukas, Dieter; Clutton-Brock, Tim
Abstract: In many mammals, breeding females are intolerant of each other and seldom associate closely but, in some, they aggregate in groups that vary in size, stability, and kinship structure. Aggregation frequently increases competition for food, and interspecific differences in female sociality among mammals are commonly attributed to contrasts in ecological parameters, including variation in activity timing, the distribution of resources, as well as the risk of predation. However, there is increasing indication that differences in female sociality are also associated with phylogenetic relationships and with contrasts in life-history parameters. We show here that evolutionary transitions from systems where breeding females usually occupy separate ranges ("singular breeding") to systems where breeding females usually aggregate ("plural breeding") have occurred more frequently in monotocous lineages where females produce single young than in polytocous ones where they produce litters. A likely explanation of this association is that competition between breeding females for resources is reduced where they produce single young and is more intense where they produce litters. Our findings reinforce evidence that variation in life-history parameters plays an important role in shaping the evolution of social behavior. Abstract : How many offspring a mother has may determine how social she can be. Phylogenetic analysis shows that, among mammals, female sociality (aggregations of breeding females) has evolved more frequently in species where mothers produce single young than in species where they produce litters.